Past, present and future of goal scoring analysis in professional soccer (Pasado, presente y futuro del análisis de goles en el fútbol profesional) - Joaquin Gonzalez Rodenas; Rodrigo Aranda Malaves; Andres Tudela Desantes; Enrique Sanz Ramirez; Josep Crespo Hervas; Rafael Aranda Malaves (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. The aim of this theoretical review is to summarize the key performance indicators and contextual variables that have been related to goal scoring in soccer, as well as to discuss the new perspectives and future challenges for the development of research studies on this topic. Firstly, situational variables such as match location, time of the game, opponent level, as well as match status have been shown to have an influence on goal scoring. Secondly, tactical factors such as the team possession type of start, starting zone, initial opponent positioning, type of attack, pass number per possession, type of assist, finishing zone and type of finishing have been described as performance indicators related to goal scoring in professional soccer. During the past, the vast majority of studies analysed tactical or technical indicators isolated from the complex and multifactorial process of creating goal scoring situations. Currently, the emergence of new research methods such as position data, network analysis, temporal patterns or mixed methods has broadened the possibilities for researchers to capture the complexity of soccer actions and interactions. Thus, some future challenges in the analysis of goal scoring in soccer should explore: a) the multidimensional evaluation of shooting effectiveness, b) the goal effectiveness of different styles of play, c) the goal-scorer’s skills, d) the further exploration of the effect of players interactions on goal scoring, e) f) the effects of training methods on goal scoring and f) the influence of contextual variables on goal scoring actions.